Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1677/joe.0.1380401
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of nutrients, insulin-like growth factors (IGFs) and IGF-binding proteins in the regulation of DNA synthesis by isolated fetal rat islets of Langerhans

Abstract: Insulin is a major regulatory hormone for optimal tissue growth and function in utero. Its continued availability to the growing fetus depends on increasing islet cell mass. The purpose of the study was to examine the interactions between nutrient availability and insulin-like growth factor (IGF) release and action during DNA synthesis by isolated fetal rat islets of Langerhans. Specifically, we wished to determine (a) whether the availability of glucose or total amino acids altered the release of endogenous I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 0 publications
1
46
1
Order By: Relevance
“…Although the heterologous human growth hormone can stimulate rat islet cell replication [16], most likely through the PRL receptor, it has only a modest effect on mouse islet cells [17]. The relatively lower mitogenic effect of IGF I in this assay, as compared with that of IGF II, is inconsistent with previous results that showed similar effects of both factors on fetal rat islets [7], and with the action of both factors through the IGF I receptor. It is possible that βTC-tet cells express IGF binding proteins that preferentially neutralize IGF I activity.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Although the heterologous human growth hormone can stimulate rat islet cell replication [16], most likely through the PRL receptor, it has only a modest effect on mouse islet cells [17]. The relatively lower mitogenic effect of IGF I in this assay, as compared with that of IGF II, is inconsistent with previous results that showed similar effects of both factors on fetal rat islets [7], and with the action of both factors through the IGF I receptor. It is possible that βTC-tet cells express IGF binding proteins that preferentially neutralize IGF I activity.…”
Section: Resultscontrasting
confidence: 89%
“…Significant mitogenic effects of hepatocyte growth factor (HGF) have been observed on human fetal and adult islets [4] and mouse islets [5]. Insulin-like growth factors (IGF) I and II, and platelet-derived growth factor, affect fetal rat islet cell growth [6,7]. IGF I has also been shown to stimulate replication of cultured rat insulinoma cells [8], and IGF II activates the growth of both normal [9] and transformed [10] mouse β cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary factors and especially the intakes of energy and protein are very important regulators of serum IGF-I concentrations and its biological activity, especially during the first months of infancy [6]. Amino acids were also reported to be more potent stimulators of IGF-I release than glucose [7]. For example, studies in 4-week-old rats showed that feeding a diet with 15 instead of 5% protein for only one week increased serum IGF-I more than 4-fold [8].…”
mentioning
confidence: 99%
“…Interestingly, IGF2 expression declines in mice and rats postnatally and this correlates with increased b-cell apoptosis in vivo (Petrik et al 1998(Petrik et al , 1999, suggesting that endogenous IGF2 exerts an early anti-apoptotic effect within native pancreatic islets. In contrast to this, in humans, IGF2 remains the most abundant IGF in circulation throughout life, the expression of which is detected in many tissues including the CNS, adrenal medulla, pancreas and purified b-cells (Han et al 1987, Bryson et al 1989, Hill 1990, Hogg et al 1993, Miettinen et al 1993, Asfari et al 1995, Bergmann et al 1996, Katz et al 1997. The post-natal decline in IGF2 expression may be a result of differences in the IGF2 gene promoter structure between humans and rodents (Foulstone et al 2005).…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%